2020
DOI: 10.1002/alz.12143
|View full text |Cite|
|
Sign up to set email alerts
|

Tackling challenges in care of Alzheimer's disease and other dementias amid the COVID‐19 pandemic, now and in the future

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
171
3
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(203 citation statements)
references
References 70 publications
(112 reference statements)
6
171
3
4
Order By: Relevance
“…Social isolation due to the corona measures was experienced by one third of symptomatic patients, and by a quarter of cognitively normal memory clinic patients. Social interactions are important for patients with cognitive complaints, as is engaging in daily recreational activities, e.g., exercise (16,17). During the corona crisis, many people sought for social connections online, but this is more difficult for patients with cognitive complaints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social isolation due to the corona measures was experienced by one third of symptomatic patients, and by a quarter of cognitively normal memory clinic patients. Social interactions are important for patients with cognitive complaints, as is engaging in daily recreational activities, e.g., exercise (16,17). During the corona crisis, many people sought for social connections online, but this is more difficult for patients with cognitive complaints.…”
Section: Discussionmentioning
confidence: 99%
“…This may be an important moderator in the effect of discontinued care on higher caregiver burden. These behavioral problems may be even more problematic, as a recent review showed that patients who exhibit aggression, wandering or disinhibition are even at higher risk of catching and spreading COVID-19 (16), triggering a vicious circle as research now shows that catching COVID-19 has adverse impacts upon the brain and cognition.…”
Section: Discussionmentioning
confidence: 99%
“…An odds ratio of 3.07 was associated with dementia in a UK biobank community study [59]. The reasons for the increased risk and mortality in patients with pre-existing dementia have been well reviewed [60]. What is perhaps not as widely appreciated is that the types of brain damage seen in COVID-19 are themselves major contributors to cognitive decline and dementia.…”
Section: The Types Of Cerebral Ischaemic Damage Seen In Covid-19 Arementioning
confidence: 99%
“…Similarly, our survey does not assess the extent to which our respondents felt that public health interventions could result in potentially negative impacts on their LTC residents. It is important to note that recommended public health interventions could result in worsening cognition and functional decline because of the restriction of external visitors and in-home recreational activities [21]. This negative impact ultimately lowers the quality of life for LTC residents, and should to be considered when planning future pandemic responses in LTC.…”
Section: Strengths and Limitationsmentioning
confidence: 99%